Physical violence against intimate partners and related exposures to violence among South African men. - Gupta, Jhumka; Silverman, Jay G; Hemenway, David; Acevedo-Garcia, Dolores; Stein, Dan J; Williams, David R (CMAJ : Canadian Medical Association journal = journal de l'Association medicale canadienne, 2008)
Despite high rates of intimate partner violence in South Africa, there have been no national studies of men's perpetration of violence against female partners.
Keywords: Adolescent; Adult; Adult Survivors of Child Abuse; Child; Cross-Sectional Studies; Domestic Violence; Female; Humans; Male; Middle Aged; Prevalence; Sex Factors; South Africa